PERANCANGAN APLIKASI AKADEMIK STMIK TIME BERBASIS ANDROIDPERANCANGAN APLIKASI AKADEMIK STMIK TIME BERBASIS ANDROID - aryanto, didik (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2021)
The development of the operating system right now cause the operating system begins to apply to smartphones in order to support the activities of the community. The Android operating system is an open source operating system which is one of the most developed operating systems and lot applied to today's smartphones. The issues examined are how to make use of the Android operating system in order to support academic activities to disseminate information to students. The methods used in this study was observational research methods. Through this method, the information gathered in accordance with the issues that will be examined. The results of this research are the android package files (APK) for the installation of the academic application for STMIK TIME's students.